Ubiquitin modification in osteogenic differentiation and bone formation: From mechanisms to clinical significance - Pan, Yuan; Tang, Yiman; Gu, Hang; Ge, Wenshu (Frontiers in Cell and Developmental Biology, 2022)
The ubiquitin–proteasome system is an important pathway for mediating posttranslational modification and protein homeostasis and exerts a wide range of functions in diverse biological processes, including stem cell differentiation, DNA repair, and cell cycle regulation. Many studies have shown that ubiquitination modification plays a critical role in regulating the osteogenic differentiation of stem cells and bone formation through various mechanisms. This review summarizes current progress on the effects and mechanisms of ubiquitin modification on transcription factors and signaling pathways involved in osteogenic differentiation. Moreover, the review highlights the latest advances in the clinical application of drugs in bone tissue engineering. A thorough understanding of ubiquitin modifications may provide promising therapeutic targets for stem cell-based bone tissue engineering.